Pendidikan Kesehatan Tentang Krisis Hipertensi Dan Penatalaksanaan Kegawat Daruratan Di Rumah - Endang Sawitri (WASATHON Jurnal Pengabdian Masyarakat, 2026)
A hypertensive crisis is a medical emergency resulting from a spike in blood pressure that can lead to target organ damage if not treated promptly. This condition is urgent due to the high incidence rate, risk of serious complications such as stroke and heart failure and death. Low public knowledge in the management of hypertension, non-compliance with taking medication, unhealthy living behavior will risk hypertension. Lack of public knowledge about emergency management in patients with hypertensive crisis at home will be fatal to the sufferer. Health education will be conducted on July 2, 2025. Place in Dusun Bancang and Tegal Gaden Village, Trucuk, Klaten. Methods with lectures, discussions. Media with Leatflet and Power Point. Evaluation tools with pre and post test questionnaires. This health education is in collaboration with partners: Trucuk II health center, Gaden Village. Health education is needed to increase awareness of the Gaden Village community in preventing hypertensive crises, strengthening early detection and management of hypertensive crises, and management of emergencies. Education can prevent more severe complications. With proper health education, the incidence and impact of hypertensive crises can be reduced, improving the quality of life of hypertensive patients and reducing the burden on public health.